Pengaruh literasi keuangan dan literasi digital terhadap penggunaan QRIS siswa kelas XI SMA Negeri Titian Teras H. Abdurrahman Sayoeti Jambi - Alfiyana, Alfiyana; Muslim, Fachruddiansyah; Putra, Iwan (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to determine the effect of financial literacy and digital literacy on the use of QRIS among 11th grade students at Titian Teras H. Abdurrahman Sayoeti State Senior High School. Financial literacy and digital literacy are two important factors in supporting the adoption of digital payment technologies such as QRIS. The method used in this study is quantitative with a survey approach, using a questionnaire as a data collection instrument. The research sample consisted of 104 eleventh-grade students selected through purposive sampling. Data analysis was conducted using multiple linear regression to test the influence of independent variables (financial literacy and digital literacy) on the dependent variable (QRIS usage). The results of the study indicate that both financial literacy and digital literacy significantly and positively influence QRIS usage. Furthermore, financial literacy and digital literacy simultaneously contribute significantly to increasing QRIS usage among students. This study concludes that improving financial and digital literacy is crucial for promoting the adoption of digital payment technology among students.